The Relationship Between The Level Of Parental Knowledge And The Assistance Of Independence Of Children With Intellectual Disabilities In Extraordinary Schools Pontianak - Safira, Annisa; Jiu, Cau Kim; Almumtahanah, Almumtahanah; Kawuryan, Uji; Ariyanti, Sri (International Journal of Health Sciences, 2025)
Every parent would expect to have a child born with good physical and mental conditions. However, not all of these expectations are achieved because some children are born with developmental problems or special needs such as intellectual disabilities. Children with intellectual disabilities require more intensive attention and assistance to be able to carry out daily activities. This study aimed to determine the relationship between the level of parental knowledge and the assistance of independence of children with intellectual disabilities in extraordinary schools Pontianak. This type of research was descriptive correlation with cross sectional design. The sample in this study consisted of 42 parents who were selected by total sampling. The data collected in this study was analyzed Chi-square test. The results of this study showed that 15 respondents (35.7%) have a moderate level of knowledge, and 24 children (57.1%) are categorized as independent. The statistical test results p value 0.000 (p ≤ 0.05. There is a relationship between the level of parental knowledge with the assistance of independence of children with intellectual disabilities in SLB Pontianak City.